Seawater carbonate chemistry and Acartia tonsa experimental evolution epigenetics - Brennan, Reid S; deMayo, James A; Finiguerra, Michael B; Baumann, Hannes; Dam, Hans G; Pespeni, Melissa H (PANGAEA, 2025)
We experimentally evolved the foundational marine copepod Acartia tonsa for 25 generations under ocean acidification, warming, and their combination and then measured epigenomic, genomic, and transcriptomic responses. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from the PANGAEA dataset (see Source). In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-09-02.
Keywords: Acartia tonsa; Animalia; Arthropoda; Bottles or small containers/Aquaria (<20 L); Coast and continental shelf; Gene expression (incl. proteomics); Laboratory experiment; North Atlantic; Other studied parameter or process; Pelagos; Single species; Temperate; Temperature; Zooplankton